A seasonal investigation of the ecto - and endoparasites of the barbel,Clarias Gariepinus (Burchell) 1822, in Lebowa, South Africa - Mashego, Sevid Ntlogeleng (University of the North, 1977)
Refer to document
Thesis (M.Sc.) - University of the North, 1977
Keywords: Ecto parasites; Endoparasites; Trematoda; Nematoda -- South Africa -- Lebowa; Gestoda -- South Africa -- Lebowa